Molecular basis for turnover inefficiencies (misses) during water oxidation in photosystem II. Issue 29 (13th July 2022) - Han, Guangye; Chernev, Petko; Styring, Stenbjörn; Messinger, Johannes; Mamedov, Fikret
Abstract : Temperature dependence of the transition inefficiencies (misses) for the water oxidation process in photosystem II were studied by EPR spectroscopy and are explained on the basis of S state dependent structural changes at the CaMn4 O5 -cluster. Abstract : Photosynthesis stores solar light as chemical energy and efficiency of this process is highly important. The electrons required for CO2 reduction are extracted from water in a reaction driven by light-induced charge separations in the Photosystem II reaction center and catalyzed by the CaMn4 O5 -cluster. This cyclic process involves five redox intermediates known as the S0 –S4 states. In this study, we quantify the flash-induced turnover efficiency of each S state by electron paramagnetic resonance spectroscopy. Measurements were performed in photosystem II membrane preparations from spinach in the presence of an exogenous electron acceptor at selected temperatures between −10 °C and +20 °C and at flash frequencies of 1.25, 5 and 10 Hz. The results show that at optimal conditions the turnover efficiencies are limited by reactions occurring in the water oxidizing complex, allowing the extraction of their S state dependence and correlating low efficiencies to structural changes and chemical events during the reaction cycle. At temperatures 10 °C and below, the highest efficiency ( i.e. lowest miss parameter) was found for the S1 → S2 transition, while the S2 → S3 transition was least efficient (highest miss parameter) over the whole temperature range. These electron paramagnetic resonance results were confirmed by measurements of flash-induced oxygen release patterns in thylakoid membranes and are explained on the basis of S state dependent structural changes at the CaMn4 O5 -cluster that were determined recently by femtosecond X-ray crystallography. Thereby, possible "molecular errors" connected to the e − transfer, H + transfer, H2 O binding and O2 release are identified.